Pingxiao pian attenuate invasiveness and proliferation of lung adenocarcinoma through regulating miR-29b-3p/TGF-β1/Smad/EMT pathway - Jie-Ni Feng; Pei-Rui Chen; Shao-Fei Yuan; Qiang Dai; Wei-E. Zheng; Hua-Long Lin (Discover Oncology)
Abstract Introduction Lung cancer is a highly prevalent and deadly disease worldwide, causing over 1.2 million deaths each year. Pingxiao Pian (PXP) tablets, a Chinese traditional medicine, have been widely applied in the treatment of lung cancer. However, the mechanism underlying therapeutic effects of PXP tablets remains undisclosed. Methods A549 human LUAD cell line was utilized for in vitro experiments. Transfection of miR-29b mimic was performed using Lipofectamine 3000. PXP was purchased and dissolved into PBS and drinking water after carefully removing the outer coating. Dual-luciferase reporter assay was conducted to assess the regulatory effect of miR-29b on TGF-β1. The protein levels of epithelial-mesenchymal transition (EMT) markers and activation of TGF-β1 pathway were characterized using immunoblotting analysis. Results PXP reduced the invasiveness and proliferation of LUAD cells by increasing miR-29b-3p expression in vitro. Overexpression of miR-29b-3p resulted in decreased cell proliferation and invasiveness, while silencing of miR-29b-3p in the A549 cells displayed the opposite effect. Moreover, PXP treatment reversed the increased cell proliferating rate triggered by miR-29b-3p silencing. Additionally, PXP was found to hamper EMT occurrence in A549 cells by regulating miR-29b-3p and reduce expression of N-cad and vimentin. Overexpression of miR-29b-3p blocked the phosphorylation of Smad2/3 and decreased TGF-β1 expression. Luciferase assay results indicated that miR-29b-3p directly regulated TGF-β1 expression. In vivo tumor formation experiments confirmed the tumor-reducing effects of PXP and the role of miR-29b in tumor progression. PXP treatment decreased tumor size and weight via regulating miR-29b-3p. Conclusion Our study suggests that PXP exerts anti-tumor effects in LUAD through the regulation of miR-29b and the inhibition of EMT via the TGF-β1/Smad2/3 pathway.